Perbedaan Nilai Fibrosis Hati Sebelum dan Setelah Terapi Antivirus Tenofovir pada Pasien Hepatitis B Kronik di RSUP M.Djamil Padang - Miftahuz Zahrah; Saptino Miro; Yusticia Katar; Fadrian; Gestina Aliska; Malinda Meinapuri (Jurnal Ilmu Kesehatan Indonesia, 2026)
Hepatitis B virus infection is a global health problem. Long-term exposure to hepatitis B virus can cause inflammation in hepatocytes leading to liver fibrosis. Liver fibrosis is a predictor of serious complications such as liver cirrhosis and hepatocellular carcinoma. One of the targets of antiviral therapy is to reduce the degree of liver fibrosis which is associated with clinical improvement in patients with chronic hepatitis B. The aim of this study is knowing the difference in liver fibrosis values before and after tenofovir antiviral therapy in chronic hepatitis B patients at M.Djamil Padang Hospital. This study was an observational analytic study using medical record data of 43 chronic hepatitis B patients who had received tenofovir antiviral therapy for 1 year. Data were analyzed with Wilcoxon test. 93% of chronic hepatitis B patients experienced a decrease in liver fibrosis values after tenofovir antiviral therapy for one year with the difference in median values before and after tenofovir antiviral therapy was 10.8 vs 6.4 kPa. There was a significant difference between liver fibrosis values before and after tenofovir antiviral therapy.